Defined Tau Phosphospecies Differentially Inhibit Fast Axonal Transport Through Activation of Two Independent Signaling Pathways - Morris, Sarah L.; Tsai, Ming-Ying; Aloe, Sarah; Bechberger, Karin; König, Svenja; Morfini, Gerardo; Brady, Scott T. (Frontiers in Molecular Neuroscience, 2021)
Tau protein is subject to phosphorylation by multiple kinases at more than 80 different sites. Some of these sites are associated with tau pathology and neurodegeneration, but other sites are modified in normal tau as well as in pathological tau. Although phosphorylation of tau at residues in the microtubule-binding repeats is thought to reduce tau association with microtubules, the functional consequences of other sites are poorly understood. The AT8 antibody recognizes a complex phosphoepitope site on tau that is detectable in a healthy brain but significantly increased in Alzheimer’s disease (AD) and other tauopathies. Previous studies showed that phosphorylation of tau at the AT8 site leads to exposure of an N-terminal sequence that promotes activation of a protein phosphatase 1 (PP1)/glycogen synthase 3 (GSK3) signaling pathway, which inhibits kinesin-1-based anterograde fast axonal transport (FAT). This finding suggests that phosphorylation may control tau conformation and function. However, the AT8 includes three distinct phosphorylated amino acids that may be differentially phosphorylated in normal and disease conditions. To evaluate the effects of specific phosphorylation sites in the AT8 epitope, recombinant, pseudophosphorylated tau proteins were perfused into the isolated squid axoplasm preparation to determine their effects on axonal signaling pathways and FAT. Results from these studies suggest a mechanism where specific phosphorylation events differentially impact tau conformation, promoting activation of independent signaling pathways that differentially affect FAT. Implications of findings here to our understanding of tau function in health and disease conditions are discussed.